2016
DOI: 10.1177/2158244016665661
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Disease Self-Management and Behavior Change Attitudes in Older Adults

Abstract: The population of older adults with chronic disease is increasing, yet little is known about their perception of chronic disease and self-management. To develop successful and sustainable chronic disease self-management interventions in the older adult population, health care providers must first understand older adults' attitudes toward health status and behavior change. This pilot study was conducted to determine the feasibility of the study design. The purpose of this pilot study was to assess the appropria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…In addition, 1019 elderly patients with an average age of 73.2 years who were taking anticoagulants had an increased risk of myocardial infarction and vascular disease or stroke/transient ischaemic attack during the median follow-up period of 33.7 months (Pastori et al, 2015). The incidence of AF increases with age (Lee, Choi, Han, Cha, & Oh, 2017), and elderly people with chronic diseases tend to have poor selfmanagement (Sell, Amella, Mueller, Andrews, & Wachs, 2016). Elderly people with AF should increase their awareness of AF and prevention of complications and learn relevant management skills (Lane et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 1019 elderly patients with an average age of 73.2 years who were taking anticoagulants had an increased risk of myocardial infarction and vascular disease or stroke/transient ischaemic attack during the median follow-up period of 33.7 months (Pastori et al, 2015). The incidence of AF increases with age (Lee, Choi, Han, Cha, & Oh, 2017), and elderly people with chronic diseases tend to have poor selfmanagement (Sell, Amella, Mueller, Andrews, & Wachs, 2016). Elderly people with AF should increase their awareness of AF and prevention of complications and learn relevant management skills (Lane et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Further, with the aging of the population, research is focusing on ways to enhance individuals’ abilities to self-manage chronic disease. To help individuals better self-manage, healthcare providers must understand clients’ attitudes toward chronic disease, health behavior change, barriers to change, and the role social support plays in the self-management process (Sell, Amella, Mueller, Andrews, & Wachs, 2016). A recent review has indicated that interventions that include self-monitoring can lead to significant reductions in specific areas of healthcare usage, but this is dependent on the characteristics of the chronic illness (McBain et al., 2015).…”
Section: Back To the Concept Of Adjustmentmentioning
confidence: 99%